Jahrbuch der Raabe-Gesellschaft (De Gruyter, 1960)
The Raabe Society Yearbook not only provides a forum for specialists working on the extraordinarily extensive narrative writings of Wilhelm Raabe himself (1831-1910) but has also developed as a conduit for general work on German Realism. Each volume contains papers and miscellaneous articles, a review section and an annual bibliography of the latest research in Raabe studies.